2003
DOI: 10.1016/s1097-2765(03)00183-7
|View full text |Cite
|
Sign up to set email alerts
|

Equal Sister Chromatid Exchange Is a Major Mechanism of Double-Strand Break Repair in Yeast

Abstract: Equal sister chromatid exchange (SCE) has been thought to be an important mechanism of double-strand break (DSB) repair in eukaryotes, but this has never been proven due to the difficulty of distinguishing SCE products from parental molecules. To evaluate the biological relevance of equal SCE in DSB repair and to understand the underlying molecular mechanism, we developed recombination substrates for the analysis of DSB repair by SCE in yeast. In these substrates, most breaks are limited to one chromatid, allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
162
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(173 citation statements)
references
References 49 publications
8
162
1
2
Order By: Relevance
“…With respect its role in HDR, genetic and physical evidence suggests that the primary function of the Mre11 complex is to promote HDR between sister chromatids via the hook and coiled-coil domains of Rad50 (Bressan et al 1999;Hartsuiker et al 2001;Gonzalez-Barrera et al 2003;Wiltzius et al 2005;Hohl et al 2011). Mre11 complex-mediated NHEJ appears to be primarily dependent on DNA-binding sites in the globular domain (Williams et al 2008(Williams et al , 2009), although we showed that the hook and coiled-coil domains also influence this process, presumably via long-range effects on the disposition of globular domain components (Hohl et al 2011).…”
mentioning
confidence: 99%
“…With respect its role in HDR, genetic and physical evidence suggests that the primary function of the Mre11 complex is to promote HDR between sister chromatids via the hook and coiled-coil domains of Rad50 (Bressan et al 1999;Hartsuiker et al 2001;Gonzalez-Barrera et al 2003;Wiltzius et al 2005;Hohl et al 2011). Mre11 complex-mediated NHEJ appears to be primarily dependent on DNA-binding sites in the globular domain (Williams et al 2008(Williams et al , 2009), although we showed that the hook and coiled-coil domains also influence this process, presumably via long-range effects on the disposition of globular domain components (Hohl et al 2011).…”
mentioning
confidence: 99%
“…for chromosomal exchanges, it is thought that BLM helicase functions in regulating HR (7)(8)(9). Also, BLM helicase is required for faithful chromosome segregation (10) and repair of stalled replication forks (11,12), the processes that are linked to HR (13)(14)(15).…”
mentioning
confidence: 99%
“…This observation suggests that, in contrast to the presumed predominant intrachromatid repair in Arabidopsis (Orel et al, 2003) and in tobacco (Siebert and Puchta, 2002), barley uses the sister chromatid in the majority of cases for repair of staggered DSBs, apparently independent of whether immediate ligation, SDSA, NHEJ, or MMHJ is followed to seal the break. A few hints that SCE could be a major pathway of DSB repair came from the observation of increased SCE frequency after treatment of mammalian cells with restriction endonucleases (Natarajan et al, 1985) and from Rad51 (recombinase)-dependent equal SCE in broken centric monoplasmids of yeast (González-Barrera et al, 2003). In contrast, in cultivated Chinese hamster cells, "the sister chromatid acts as a repair template in a substantial proportion of DSB repair events," but "the outcome.is primarily gene conversion unassociated with reciprocal exchange" (Johnson and Jasin, 2000).…”
Section: Discussionmentioning
confidence: 99%